Modelling Pollutant Dispersion in Urban Canyons to Enhance Air Quality and Urban Planning - Francisco Ruda Sarria; MCarmen Guerrero Delgado; Rafael Monge Palma; Teresa Palomo Amores; José Sánchez Ramos; Servando Álvarez Domínguez (Applied Sciences)
Air pollution in urban street canyons presents a serious health risk, especially in densely populated areas. While previous research has explored airflow characteristics in these canyons, it often lacks detailed data on pollutant dispersion and the effects of wind speed on airflow patterns and vortex formation. This study uses Computational Fluid Dynamics (CFD) to deliver quantitative measurements of pollutant dispersion rates and qualitative insights into airflow patterns across various street canyon morphologies. The analysis examines a range of aspect ratios (ARs), from wide (AR = 0.75) to narrow (AR = 4.5), and different wind speeds to evaluate their effects on pollutant dispersion. Findings indicate that purging flow rates decline as the AR increases, with a more pronounced decrease at lower AR values. In narrower streets, airflow patterns are particularly sensitive to wind velocity, leading to unexpected vortices that hinder effective pollutant dispersion. By incorporating these insights into urban design strategies, cities can enhance street ventilation, thereby reducing pollutant concentrations and improving public health. This study also tests a specific street layout in Seville to predict pollutant accumulation under various conditions, assessing health risks based on World Health Organization guidelines. Ultimately, this research aids in developing healthier, more sustainable urban environments.